The impact of anaesthesia upon the main functions of the animal organism - Năstasă V.; Mariana Grecu (Medicamentul Veterinar, 2007)
The general anesthetics produce the reversible loss of consciousness and sensitivity and influence the vital functions of the organism. More than a century ago, the anesthetic was considered to be a poison which intoxicates the nervous system. Recently, it has been proved that the anesthetic substance invades all tissues. Despite these drawbacks, they are widely used in the experimental researches “in vivo”, but their use may considerably change the result of the physiological or pharmacological effects of these substances; thepharmacological details are few. The aim of this communication is to provide information referring to the interactions between general anesthetics and other pharmacological agents, limiting at the substances currently used in the experimental research.